Study on the Electro-Optical Properties of Polymer-Dispersed Liquid Crystals Doped with Cellulose Nanocrystals - Jiayan Wang; Yan Qiao; Ziyi Yang; Yue Han; Hui Zhang; Zhiguang Li; Guili Zheng; Yanjun Zhang; Lizhi Zhu (Molecules)
The present study focuses on the effect of doping KH560-modified cellulose nanocrystals (CNCs) on the electro-optical characteristics of polymer-dispersed liquid crystals (PDLCs). PDLC films were fabricated through the polymerization-initiated phase separation (PIPS) process and doped with CNC nanoparticles at various concentrations. At low concentrations, the CNCs at the interface, by virtue of their unique chiral characteristics, induce an orderly arrangement of liquid crystal molecules. Meanwhile, the interaction between the film’s fiber structure and the liquid crystal droplets brings about an augmentation in the arrangement efficiency. The excellent dispersion of CNCs diminishes the random alignment of liquid crystal molecules and mitigates light scattering. Additionally, it aids in the deflection of the liquid crystal director, facilitating the lubrication of the liquid crystals’ movement. It is remarkable that within the range of relatively lower CNCs doping concentrations, specifically from 0.005 wt% to 0.05 wt%, the PDLC films exhibit lower threshold and saturation voltages, faster response, enhanced viewing angle performance and higher contrast.